The Impact of Agricultural E-Commerce on Smallholder Incomes and Supply Chains: Evidence from Garut, West Jawa - Diana Magfiroh; Kiflu Chekole Tekle; Ginna Novarianti Dwi Putri Pramesti (Politeknik Siber Cerdika Internasional, 2025)
The rapid development of digital technology has created new opportunities to improve agricultural marketing systems, particularly for smallholder farmers who often face limited market access and long supply chains dominated by intermediaries. This study investigated the influence of agricultural e-commerce on enhancing the income of smallholder farmers and developments in the supply chain in the Garut region of West Java. The present study collected and analyzed quantitative and qualitative data using a mixed-method approach, surveying 250 smallholder farmers who use e-commerce platforms. It was found from the results that the adoption of e-commerce significantly increased farmers' monthly income from an average of 2.85 million to 4.15 million rupiah. The structure of the supply chain has also altered, with a significant reduction in the number of intermediaries from 3-4 to 1-2 intermediaries. Conversely, farmers' shares of the final price of products in cases such as organic vegetables have increased by 78 percent. Regression analysis further verified that factors such as education level, digital literacy, and the reduction of intermediaries have contributed most to explaining income changes. Though the findings showed the relative success of these platforms, some major challenges were pinpointed, such as logistics costs at a score of 4.6 and limited digital literacy at a score of 4.2. This paper concludes that agricultural e-commerce development relies on simultaneous consideration of the three axes: logistics infrastructure development, enhancement of digital capability by farmers, and adjustment in cultivation patterns.